Psikoedukasi: Upaya Mengoptimalkan Screen Time Gadget pada Anak Melalui Pola Asuh Positif - Maria Ulfiyana; Alfi Purnamasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Psychoeducation is provided to the community as a form of community service through interactive socialization to increase people's understanding of certain themes. In this activity, the theme raised and discussed was how to optimize gadget screen time through positive parenting patterns. The targets for providing this psychoeducation are all levels of society in a village in Central Java, especially parents. The methods used in psychoeducation include: 1) lecture, 2) presenting videos, 3) discussion (question and answer), and 4) pretest dan posttest. Based on the results of the Wilcoxon test analysis of the first and second psychoeducational presentations, it showed that there was a significant change in the participants' understanding of the psychoeducational material that had been provided by the presenters.